PENGARUH PROMOSI DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MEREK HONDA - Citra Suci Mantauv (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2017)
The purpose of this research is to determine the influence of Promotion and Locations of purchasing decisions. The sample used in this research is 100 people. Sampling in this research is based on convenience sampling technique. The analysis model used is multiple linear regression. With the constant value (α) is 8.418 while the value of Promotion coefficient 0.367 and the locataion of 0.432. Based on the results of data analysis with multiple linear regression known that the R-squre value of 0.773. Test f shows the two variables indenpenden have a positive and significant effect on the dependent variable.